Mutant of Escherichia coli with Thermosensitive Protein in the Process of Cellular Division - Nagai, Kazuo (1972)
A new thermosensitive mutant of Escherichia coli deficient in cell division was isolated by means of membrane filtration after nitrosoguanidine mutagenesis. The mutant cells grow normally at 30 C but stop dividing immediately after shift to 42 C, resulting in multinucleated filaments lacking septa. The number of colony-forming units does not decrease for at least 6 hr at 42 C. The maximum length of the filaments is 10 to 16 times that of normal cells. Addition of a high concentration of NaCl fails to stimulate cell division at 42 C. The filaments formed at 42 C divide abruptly 30 min after shift to 30 C, and synchronous increase of cell number is shown for 3 hr. The macromolecular synthesis of protein and nucleic acids at 42 C is normal on the whole. The cell division shown after the shift from 42 to 30 C is observed in the absence of thymine, but not in the presence of chloramphenicol or in a medium deficient in amino acids. However, the filament can divide to some extent in the presence of chloramphenicol if some protein synthesis is allowed to proceed at 30 C before the addition of the antibiotic. The elongated cells divide at 42 C provided that they are exposed to 30 C before being shifted to high temperature.